Self-Reported Antenatal Medicines Use Among Women Living with and Without HIV in Western Cape, South Africa: A Sub-Analysis of the B Positive Cohort Study - Elzouki, Zaineb (Department of Medicine, 2023)
Globally, innumerable women take medication while they are pregnant, and this trend is growing. The pipeline of medicines targeting maternal comorbidities is expanding. However, for most medicines, there is insufficient data on their safety in pregnancy. In addition, women may be taking medication for chronic or acute conditions before they recognize that they are pregnant. This study compared the self-reported pattern of medicine use during the course of pregnancy in a cohort of pregnant women either living with or without HIV; seeking care at Gugulethu primary health care obstetric clinic in Western Cape, South Africa. Data on medicine use was collected over 3 antenatal visits. Medications reported were manually classified and coded by a clinical pharmacist and medical doctor. Structured interviews using a detailed questionnaire on medication use were administered to n=989 pregnant women. Women who had an ectopic pregnancy or an elective termination of pregnancy (TOP) were excluded from the analysis. 982 of these women were included in our analysis (n=507 HIV-negative and n=475 HIV positive). Of these, 39 (4.0%) did not report taking any medicine during pregnancy. Most 907 (92.3%) pregnant women reported using at least one over-the-counter medicine (OTC) and the majority, 601 (61.2%), at least one prescription medicine. A total of 36 (3.7%) reported using at least one herbal or traditional medicine over the course of the pregnancy. Pregnant women living with HIV were significantly less likely to report use of OTC medicine (56.2% vs 77.7%, p=<0.001). Pregnant women living with HIV also reported less herbal medicine use (2.9% vs 4.7%, p=0.07) compared to pregnant women living without HIV, though the effect was non-significant within this sample. Excluding antiretroviral medicines, prescription medicine use was essentially the same among pregnant women living with and without HIV (30.5% vs 30.2%, p=0.96). Exposure to medicines known to be potentially teratogenic or unsafe in pregnancy was reported in 300 (30.65%) pregnant women, with aspirin 238 (24.2%) and nonsteroidal anti-inflammatory medicines 46 (4.7%) medicines being the most reported. This study provides valuable information on self-reported medication use among pregnant women living with and without HIV in a South African primary healthcare setting. Medicine use was widespread in the study cohort, particularly OTC, with high prevalence of potentially unsafe medicines used during pregnancy. Our finding highlights the urgent need to build awareness around rational and safe medicine use among antenatal staff; pharmacists; and women of child-bearing age in South Africa, encouraging the taking of a thorough history of medicine exposure throughout the antenatal period.